Patient reports of the outcomes of treatment: a structured review of approaches. - Lloyd, H; Jenkinson, C; Hadi, M; Gibbons, E; Fitzpatrick, R (2014)
Patient reports or ratings are essential for measuring the quality of patient care. Measures designed for this purpose tend to focus on the processes and structures of care rather than the outcomes of it. The latter is arguably the most valid indicator of the quality of care patients receive. Typically this information is gathered by probing patient satisfaction with treatment as part of an investigation of satisfaction with hospital care. More recently patient ratings of the outcome of treatment have been obtained to measure treatment efficacy in clinical trials. However, a more direct approach is to ask patients to assess the benefit of treatment on their current health status. We performed a structured literature review on patient reported satisfaction with outcomes of treatment and direct patient assessments of the same. The purpose of this was to identify suitable candidate questions for a short instrument to tap patient evaluations of in-patient hospital interventions. Articles were included if they dealt with patient satisfaction or patient assessment of the outcomes of treatment. Articles were excluded if they dealt more generally with patient satisfaction with care. We identified 169 papers, 79 were included in the review. The findings of this review suggest that there are a number of benefits of directly asking patients to assess the outcome of hospital treatment. Importantly this approach reflects outcomes relevant to the patient and is also more likely to reflect patient report in routine clinical practice. There is also evidence that such approaches have face validity and construct validity. The problems associated with this approach (i.e. response bias), are those common to patient reported outcome surveys, but employing appropriate strategies can minimize them. Furthermore, employing a simple set of questions that asks patients to assess the outcomes of treatment they receive can be time and resource efficient in comparison to administering lengthy measures. This approach could be tested for potential generic use as an evaluative measure for patients in hospital settings.